Active Virtual Reality for Chronic Primary Pain: Mixed Methods Randomized Pilot Study - Tuck, Natalie; Pollard, Catherine; Good, Clinton; Williams, Caitlin; Lewis, Gwyn; Hames, Murray; Aamir, Tipu; Bean, Debbie (JMIR Publications, 2022)
Background: The modern management of chronic pain is largely focused on improving functional capacity (often despite ongoing pain) by using graded activation and exposure paradigms. However, many people with chronic pain find functional activation programs aversive, and dropout rates are high. Modern technologies such as virtual reality (VR) could provide a more enjoyable and less threatening way for people with chronic pain to engage in physical activity. Although VR has been successfully used for pain relief in acute and chronic pain settings, as well as to facilitate rehabilitation in conditions such as stroke and cerebral palsy, it is not known whether VR can also be used to improve functional outcomes in people with chronic pain. Objective: This study aimed to assess the feasibility of conducting an adequately powered randomized controlled trial (RCT) to test the efficacy of VR in a chronic pain treatment center and assess the acceptability of an active VR treatment program for patients in this setting. Methods: For this mixed methods pilot study, which was designed to test the feasibility and acceptability of the proposed study methods, 29 people seeking treatment for chronic pain were randomized to an active VR intervention or physiotherapy treatment as usual (TAU). The TAU group completed a 6-week waitlist before receiving standard treatment to act as a no-treatment control group. The VR intervention comprised twice-weekly immersive and embodied VR sessions using commercially available gaming software, which was selected to encourage movement. A total of 7 VR participants completed semistructured interviews to assess their perception of the intervention. Results: Of the 99 patients referred to physiotherapy, 53 (54%) were eligible, 29 (29%) enrolled, and 17 (17%) completed the trial, indicating that running an adequately powered RCT in this setting would not be feasible. Despite this, those in the VR group showed greater improvements in activity levels, pain intensity, and pain interference and reported greater treatment satisfaction and perceived improvement than both the waitlist and TAU groups. Relative effect sizes were larger when VR was compared with the waitlist (range small to very large) and smaller when VR was compared with TAU (range none to medium). The qualitative analysis produced the following three themes: VR is an enjoyable alternative to traditional physiotherapy, VR has functional and psychological benefits despite continued pain, and a well-designed VR setup is important. Conclusions: The active VR intervention in this study was highly acceptable to participants, produced favorable effects when compared with the waitlist, and showed similar outcomes as those of TAU. These findings suggest that a confirmatory RCT is warranted; however, substantial barriers to recruitment indicate that incentivizing participation and using a different treatment setting or running a multicenter trial are needed.
Keywords: VR; acceptability; chronic pain; feasibility; intervention; pain management; physiotherapy; rehabilitation; serious games; virtual reality; 32 Biomedical and Clinical Sciences; 4201 Allied Health and Rehabilitation Science; 4203 Health Services and Systems; 3202 Clinical Sciences; 42 Health Sciences; Behavioral and Social Science; Rehabilitation; Complementary and Integrative Health; Physical Rehabilitation; Health Disparities; Comparative Effectiveness Research; Neurosciences; Physical Activity; Clinical Trials and Supportive Activities; Pain Research; Chronic Pain; Health Disparities and Racial or Ethnic Minority Health Research; Clinical Research; Networking and Information Technology R&D (NITRD); 6.6 Psychological and behavioural; 6.7 Physical; 7.1 Individual care needs; Musculoskeletal